Preschoolers' reasoning about numbers in picture books. Issue 3 (2nd July 2020) - Björklund, Camilla; Palmér, Hanna
ABSTRACT: In this article we report on a study of children's attention to numerical content in picture books. Specific research questions are 1) how the content in a designed picture book directs children's attention to numbers, and 2) what kind of numerical reasoning the book reading entails. To answer these questions, we conducted an educational design research study in two cycles, with a specially designed picture book and two ways of reading: first without any prompting from the reading teacher, and second with teacher-child interaction. Nineteen preschool children (aged 3–5 years) and three teachers participated in video-observed individual reading sessions. The observations of the reading activities were analyzed with focus on the children's attention to numbers as well as on their numerical reasoning during the book talks. Based on the observations, we suggest that preschool children do direct their attention to aspects of numbers, but that the design of the pictures and the framing of the reading sessions influence which numerical aspects are discerned. Furthermore, teachers' support in transforming empirical clues into mathematical representations and comparisons seems critical for more advanced reasoning about numbers to occur.